Monte Carlo simulation of proton track structure in biological matter - Quinto, Michele Arcangelo (2017)
Abstract: Understanding the radiation-induced effects at the cellular and subcellular levels remains crucial for predicting the evolution of irradiated biological matter. In this context, Monte Carlo track-structure simulations have rapidly emerged among the most suitable and powerful tools. However, most existing Monte Carlo track-structure codes rely heavily on the use of semi-empirical cross sections as well as water as a surrogate for biological matter. In the current work, we report on the up-to-date version of our homemade Monte Carlo code TILDA-V – devoted to the modeling of the slowing-down of 10 keV–100 MeV protons in both water and DNA – where the main collisional processes are described by means of an extensive set of ab initio differential and total cross sections. Graphical abstract: [Figure not available: see fulltext.].